Immissionsökologische Untersuchungen in Tucuman/Nordwestargentinien - Endlicher, Wilfried; Schultz, Eckart (ERDKUNDE, 1996)
Over a two year period weekly integrating measurement of suspended particulate matter and nitrogen dioxide was carried out in Tucuman using the Sigma-2 sampler of the German Weather Service. The particle concentration based on deposition sampling and subsequent microscopical analysis is given for coarse (12-48 µm) and fine (3-12 µm) fraction of airborne dust. Acid sulfate and nitrate particles have been determined by ionchromatography. Nitrogen dioxide was sampled by diffusion tubes and determined ionchromatographically as well. The dust load shows marked seasonal variations with maximum values during the dry winter months. The peaks considerably exceed German comparative values. The pronounced sulfate load may have adverse effects on health. Nitrogen dioxide values, however, are lower than in Central Europe. In conclusion, measures are recommended to improve air quality conditions in Tucuman.